PENINGKATAN AKTIVITAS DAN HASIL BELAJAR PKn MELALUI METODE PEMBELAJARAN KOOPERATIF â€œBERKIRIM SALAM DAN SOALâ€ DI SMP KARTIKA 1-6 PADANG - Nova, Fitria (Fakultas Ilmu Sosial Universitas Negeri Padang, 2014)
This study aims to determine if cooperative learning in the form of exchanging greetings and questions may increase the activity and learning outcomes of students in the subjects of Citizenship education at SMP Kartika 1-6 Padang. This study was a classroom action research with the research subjects were students of class VIII/3 SMP Kartika 1-6 Padang. Data were collected through observation using observation sheet, test, and interview. This study was conducted in two cycles. The results of this study indicate that the learning process by using the cooperative learning method in the form of exchanging greetings and questions may increase the activity and learning outcomes of students. Based on observations, it appears that student learning activities during the learning process in the cycle I and II was increased. Similarly, the learning outcomes of students at pretest and posttest on each cycle. Key Words: Learning activity, learning outcomes, cooperative method